Influence of temperature combined with photodynamic inactivation on the development of Aedes aegypti - Matheus Garbuio; Alessandra Ramos Lima; Kamila Jessie Sammarro Silva; Mariana De Souza; Natalia Mayumi Inada; Lucas Danilo Dias; Vanderlei Salvador Bagnato (Photodiagnosis and Photodynamic Therapy)
To reduce the speed of selection of populations resistant to chemical insecticides, photodynamic inactivation (PDI) against Aedes aegypti is a hot-topic and promising alternative technique to vector control. Temperature is an important factor in the survival of Ae. aegypti larvae and mosquitoes as it influences physiology, behavior, and ecology. This work aimed to evaluate parameters of the biological cycle of Ae. aegypti such as: hatching rate, larval development, adult mosquito longevity, sex ratio, weight, and lethal concentration of larval mortality (LC) through the combination of PDI with different temperatures. The number of larvae found after 48 h suggests that temperature affects hatching rate. Additionally, results showed a delay in development of surviving larvae after PDI when compared to control groups, and there was a reduction in the longevity of mosquitoes that undertook photodynamic action. PDI also led to a predominance of male insects, and observed weight indicates that the inactivation method may have also interfered in mosquito size. The results point to a satisfactory performance of PDI at all tested temperatures. Experimental conditions that were not lethal to all larvae implied that PDI impacts the mosquitoes’ biological cycle. Though metabolism and development are improved at higher temperatures, so is PDI action, thus maintaining the net benefit. Therefore, it is assumed that the proposed photolarvicide can be useful in reducing arbovirus transmission, and results invite for future research in different abiotic conditions.